Influence of marine fuel properties on ignition, injection delay and energy efficiency - Sergejus Lebedevas (Vilnius Gediminas Technical University, 2021)
According to the International Council on Combustion Engines (CIMAC) and International Maritime Organization (IMO) statistics, the rational selection of Marine Bunker Fuel (MBF) properties is an effective way to improve operating conditions and energy efficiency of all types of marine Diesel Engines (DEs). The publication presents the results of studies on the influence of heavy and distillate MBF properties on the characteristics of different DE types: high-speed (Caterpillar 3512B, MTU 8V 396TB), medium-speed (SKL VDS 48/42, ChN 26.5/31) ir low-speed (MAN B&W 6S60MC). The aim of work is to form a methodological framework for assessing the influence of marine fuel properties on the energy performance of different types of ship power plants. Numerical methods show that in the case of unfavourable selection of the density and viscosity of marine fuels regulated by the standard ISO 8217:2017, the changes in specific fuel consumption be reach up to 10% low-speed, 4…7% medium-speed, and 2…3% high-speed DEs. As the density varies from light grades to 1010 kg/m3, the change in be is 3…4%. At low viscosity, as the density increases to 1030 kg/m3, the low-speed engine comparative fuel consumption increases by 5%. It is recommended not to use fuel with a density >1010 kg/m3 and a viscosity <300…400 mm2/s. Developed solutions for the rational selection of bunkered marine fuel properties for a specific DE model trough the influence of density and viscosity on fuel injection and combustion characteristics based on multiparametric diagrams of relative fuel consumption change.